TRADISI NGEJOT: POSITIVE RELATIONSHIP ANTAR UMAT BERAGAMA - Sepma Pulthinka Nur Hanip; Muhammad Yuslih; Laesa Diniaty (Potret Pemikiran, 2020)
ABSTRACT Tradition ngejot has a very strategic role in an effort to take care of harmony between the Hindus and Islam in Lombok. Religious sentiments and cultural differences can be put together in a tradition that produce a positive relationship in the form of mutual care, tolerance, and uphold humanity as the container of happiness. This study aims to trace the history and basic principles of the tradition ngejot between the Sasak and Balinese in Lombok as an effort to knit the harmony for the happiness for the followers of the religion. In recent years, the tradition of ngejot almost never applied between the two religions. methods research using qualitative-descriptive approach of psychology and sociology. Technique of collecting data done by observation, interview, and documentation. The procedure of data analysis refers to the framework of Milles and Huberman. The results of the research about the traditions ngejot this ie. (1). Tradition ngejot have the value of a long history as a means of harmony among religions and cultures with reference to the basic principles of each religion. (2). Tradition ngejot in addition to fostering a sense of tolernasi and harmony, as well as a means to the happiness of religion.(3) filing it with the value of tradition ngejot caused by the modernization which is characterized by technology such as social media and the lack of understanding of religious and local culture. Keywords: Ngejot Tradition; Positive Relationship; Happiness; Modernization       ABSTRAKTradisi ngejot memiliki peran yang sangat strategis sebagai upaya untuk merawat harmoni antara umat Hindu dan Islam di Lombok. Sentimen agama dan perbedaan budaya dapat disatukan dalam sebuah tradisi yang menghasilkan positive relationship berupa sikap saling peduli, toleransi, dan menjunjung tinggi kemanusiaan sebagai wadah kebahagiaan.  Penelitian ini bertujuan untuk melacak sejarah dan prinsip dasar dari tradisi ngejot antara masyarakat Suku Sasak dan Bali di Lombok sebagai upaya merajut harmoni untuk kebahagiaan bagi para pemeluk agama. Dalam beberapa tahun belakangan ini, tradisi ngejot hampir tidak pernah diterapkan antara dua pemeluk agama. metode penelitian menggunakan kualitatif-deskriptif dengan pendekatan psikologi dan sosiologi. Teknik pengumpulan data dilakukan dengan cara observasi, wawancara, dan dokumentasi. Prosedur analisis data mengacu pada kerangka Milles dan Huberman. Hasil dari penelitian tentang tradisi ngejot ini yaitu. (1). Tradisi ngejot memiliki nilai sejarah yang panjang sebagai sarana harmoni antar agama dan budaya dengan mengacu pada prinsip-prinsip dasar agama masing-masing. (2). Tradisi ngejot selain memupuk rasa tolernasi dan harmoni, sekaligus sarana untuk kebahagiaan pemeluk agama.(3) mengikisnya nilai tradisi ngejot disebabkan oleh modernisasi yang bercirikan tekhnologi seperti media sosial dan kurangnya pemahaman keagamaan dan budaya lokal. Kata kunci: Tradisi Ngejot; Positive relationship; Kebahagiaan; Modernisasi